2003
DOI: 10.1002/ajh.10361
|View full text |Cite
|
Sign up to set email alerts
|

D‐dimer assay in Gaucher disease: Correlation with severity of bone and lung involvement

Abstract: The D-dimer assay as a marker of cross-linked fibrin may also be an indicator of active microvascular thrombosis, even in patients without overt hypercoagulation. In type I Gaucher disease, there is tremendous phenotypic variability that cannot be ascribed solely to different genotypes. Thus, there are no predictive tests to ascertain patients at risk for bone involvement, such as avascular necrosis, or lung disease, particularly pulmonary hypertension, which are two of the major causes of morbidity in Gaucher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…These alterations may explain the high incidence of vascular accidents in GD like avascular necrosis and pulmonary hypertension. The results of a recent study [9] hypothesize that microthrombi may be part of the etiology for avascular necrosis as well as pulmonary hypertension in patients with GD and enoxaparin might be beneficial to prevent their appearance or recurrence. We hypothize a similar pathogenesis for the retinal artery occlusion of our patient.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These alterations may explain the high incidence of vascular accidents in GD like avascular necrosis and pulmonary hypertension. The results of a recent study [9] hypothesize that microthrombi may be part of the etiology for avascular necrosis as well as pulmonary hypertension in patients with GD and enoxaparin might be beneficial to prevent their appearance or recurrence. We hypothize a similar pathogenesis for the retinal artery occlusion of our patient.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothize a similar pathogenesis for the retinal artery occlusion of our patient. Furthermore, it has been previously reported that GD may be accompanied by low grade subclinical inflammation on the wall of the vessels [9,10]. Corticosteroids might have influenced and down-modulated this low-grade inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…Cette compression vasculaire entraîne une ischémie qui selon la localisation favorise soit l'ostéonécrose épiphysaire (avec possibilité d'effondrement de l'os sous-chondral et donc de la surface articulaire favorisant une arthrose secondaire) soit un infarctus osseux métaphysaire ou diaphysaire (dont la cicatrisation s'associe à des calcifications intramédullaires périphéri-ques du territoire nécrosé, calcifications définitives et bien visibles sur les radiographies standards). Outre la compression vasculaire extrinsèque, d'autres mécanis-mes favorisant l'ischémie ont été incriminés : des vasospasmes liés à une synthèse focalisée de cytokines pro-inflammatoires [4], des troubles de la coagulation prothrombotiques in situ [5] ou des hémorragies localisées intra-osseuses [6] spontanées ou post-traumatiques favorisées par exemple par une thrombopé-nie. À noter que la cicatrisation d'une ischémie osseuse se fait en périlésionnel par un tissu de granulation hypervascularisé et que cette hyperhémie peut favoriser des surinfections secondaires avec ostéomyélite [4].…”
Section: Physiopathologie Des Lésions Ostéoarticulairesunclassified
“…Absent or reduced enzymatic activity leads to accumulation of GLC in various cells of the macrophage-monocyte system (Gaucher cells) [6,7]. Classically, the pathophysiology of Gaucher disease has been attributed to the amount, location and rate of accumulation of the stored material [8,9]. The manifestations of Gaucher disease occurring due to accumulation of Gaucher cells in three main anatomical compartments, namely the osseous skeleton, the bone marrow and visceral organs [4,10].…”
Section: Introductionmentioning
confidence: 99%